2013
DOI: 10.1080/09581596.2013.814761
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing it for themselves’: a qualitative study of children’s engagement with public health agendas in New Zealand

Abstract: In this paper, we examine how New Zealand children engage with public health agendas that seek to shape their understandings of health. We shed light on the ways children make sense of what they see, hear and come to know through public health 'work', and consider what effects this has for how they come to think of their 'selves' and relations with others. We pay attention to the way public health messages assemble, bolstered by dispositions, behaviours and ruminations expressed in schools, families and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…We begin by focusing on the seemingly positive, or at least benign, apparent inclusion of individuals from marginalized backgrounds in the texts. We then augment and complicate the apparent embracing of diversity by discussing specific patterns in the way representations of sexuality, gender, and racial diversity in the texts may subtly communicate normative and controlling health messages (see Burrows & McCormack, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We begin by focusing on the seemingly positive, or at least benign, apparent inclusion of individuals from marginalized backgrounds in the texts. We then augment and complicate the apparent embracing of diversity by discussing specific patterns in the way representations of sexuality, gender, and racial diversity in the texts may subtly communicate normative and controlling health messages (see Burrows & McCormack, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…We further encourage educators and teacher educators to engage their students in assessing their chosen or assigned textbooks for racial, gender, sexual, and ability diversity (see Foster, 2012). Teachers may also further discuss with young people the messages they are deriving from health textbooks, as Burrows and McCormack (2014) have suggested, "a critically informed variety of public health could provide opportunities for children to come to know health as more than simply eating the right foods and running a lot" (p. 159).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burrows and her colleagues found that eight-and nine-year-olds (Year 4) and 12-and 13-year-olds (Year 8) seem to have accepted discourses associating physical activity, fitness and health with guilt and selfmonitoring of the body (Burrows et al, 2002). These children had knowledge of the messages widely publicized through popular and professional mediums 'citing eating, exercise and hygiene practices as the most important health promoting behaviours' (Burrows et al, 2009: 157), but not necessarily the capacity to think through them, and determine how to relate them to their own lives (Burrows and McCormack, 2014). Kirk and Macdonald (1998: 376) argue that 'learning is an active process in which the individual seeks out information in relation to the task at hand and the environmental conditions prevailing at any given time, and tests out her or his own capabilities with the context formed by the task and the environment'.…”
Section: Students' Perspectivesmentioning
confidence: 95%
“…Burrows and her colleagues found that eight- and nine-year-olds (Year 4) and 12- and 13-year-olds (Year 8) seem to have accepted discourses associating physical activity, fitness and health with guilt and self-monitoring of the body (Burrows et al, 2002). These children had knowledge of the messages widely publicized through popular and professional mediums ‘citing eating, exercise and hygiene practices as the most important health promoting behaviours’ (Burrows et al, 2009: 157), but not necessarily the capacity to think through them, and determine how to relate them to their own lives (Burrows and McCormack, 2014).…”
Section: Introductionmentioning
confidence: 99%